TEACHING LINGUISTICS AND LITERARY STYLISTICS IN ENGLISH LESSONS - Abduvoitov Ravshanbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Offer students specific guidelines for annotation. For example, instruct them to underline or highlight notable phrases, circle unfamiliar vocabulary, draw arrows to indicate relationships, or use symbols to represent different linguistic or stylistic elements. Encourage them to write comments or explanations in the margins.